2012
DOI: 10.1007/s10973-012-2328-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper addition on glass transition of silicate–phosphate glasses

Abstract: Glass transformation effect of mixed SiO 2 -P 2 O 5 -K 2 O-MgO-CaO-CuO glasses was studied by DSC, XRD, SEM, and Raman spectroscopy methods. The relationship between the parameters characterizing glass transformation effect and an amount of phosphorous and copper forming the glassy structure was discussed. It was shown that an increasing content of phosphorous increased solubility of copper in the structure of the studied glasses which was the result of P-O-Cu bonds formation. Degree of changes of T g , Dc p ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…The introduction of alkaline elements forms discontinuities in the vitreous network and decreases the viscosity of a glass [81]. Moreover, alkaline oxides (e.g., Na 2 O) sharply reduce the glass transition temperature of a glass [82], whereas alkaline-earth oxides (e.g., CaO) have a lower impact on the glass transition temperature [83]. The principal intermediate elements in glass oxides are Al, Fe, Ti, Ni, and Zn [84,85].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The introduction of alkaline elements forms discontinuities in the vitreous network and decreases the viscosity of a glass [81]. Moreover, alkaline oxides (e.g., Na 2 O) sharply reduce the glass transition temperature of a glass [82], whereas alkaline-earth oxides (e.g., CaO) have a lower impact on the glass transition temperature [83]. The principal intermediate elements in glass oxides are Al, Fe, Ti, Ni, and Zn [84,85].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…It indicated that the introduction of CuO was assumed to convert the bridging oxygen bonds into nonbridging oxygen bonds in the lithium silicate glass network. Justyna Sułowska et al [20] reported the similar behavior in SiO 2 -P 2 O 5 -K 2 O-MgO-CaO-CuO glasses. Takebe et al [21] reported that the T g , CTE, and molar volume decreased with increasing CuO dopant concentration.…”
Section: Introductionmentioning
confidence: 73%
“…Justyna Sułowska et al presented that the T g decreased as the CuO concentration increased in SiO 2 -P 2 O 5 -K 2 O-MgO-CaO-CuO glasses. Because the more covalent character of Cu 2+ -O bonds replaced the more ionic bonds, such as Ca-O bonds and Mg-O bonds, this caused the glass structure to be more rigid, which resulted in the increasing amount of stress in the glass and thus, the T g decreased [20]. H. Takebe et al reported that the T g , CTE, and molar volume decreased with increasing CuO concentration in the CuO-BaO-B 2 O 3 -P 2 O 5 glass system [21].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to take the amorphous form also depends on the kind of introduced modifiers [16,17]. The works [18][19][20] show that it is possible to add up to 80 mol% of ZnO into the structure of the glasses from the system P 2 O 5 -ZnO.…”
Section: Introductionmentioning
confidence: 99%